(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2026)
This study explores the effectiveness of an interdisciplinary, lab-based teaching approach in a master’s-level physics course through the synthesis (using co-precipitation method) and characterization of Ferrum doped Co–Ni nanocomposites. The laboratory integrates physics, chemistry, and materials science to enhance student learning, engagement, and problem-solving skills. Data from 20 master’s students over one semester reveal significant improvements in conceptual understanding, lab skills, and the ability to connect theory with practice. Quantitative statistical analysis demonstrated enhanced performance and engagement when compared to traditional lecture-based teaching.